Model Project Based Learning (PjBL) Berbasis Lesson Study Terhadap Kemampuan Berpikir Kreatif Siswa SMA - Chusnul Fauziah; Duwi Nuvitalia; Ernawati Saptaningrum (Universitas PGRI Semarang, 2018)
The phenomenon of students receiving learning materials from teachers using only lecture methods to make students less creative in thinking, learning and developing self-ability. So designed a study that can improve students' creative thinking ability. The learning model used is Project Based Learning with Lesson Study. The research instrument used was pretest-posttest with 8 questions analyzed using normality test and homogeneity test. Based on the t-test on the pretest-posttest value of the experimental class using Wilcoxon method obtained Asymp result. Sig. (2-tailed) = 0 <a= 0,05 so it can be concluded that there is influence of project based learning model based on Lesson Study on students' creative thinking ability. Then after the learning model is applied, the creative thinking ability of the students increases which initially less creative becomes creative. This is based on the Gain Test which shows the value of <g> 0.90> 0.70 means that students' creative thinking ability is included in the high category. In addition, the use of Lesson Study to support the implementation and success of learning of Project Based Learning students in the classroom. Therefore, the learning model of Project Based Learning is worth considering to be applied in school learning with other physics material.